2015
DOI: 10.3390/ma8030850
|View full text |Cite
|
Sign up to set email alerts
|

Improved Resin–Zirconia Bonding by Room Temperature Hydrofluoric Acid Etching

Abstract: This in vitro study was conducted to evaluate the shear bond strength of “non-self-adhesive” resin to dental zirconia etched with hydrofluoric acid (HF) at room temperature and to compare it to that of air-abraded zirconia. Sintered zirconia plates were air-abraded (control) or etched with 10%, 20%, or 30% HF for either 5 or 30 min. After cleaning, the surfaces were characterized using various analytical techniques. Three resin cylinders (Duo-Link) were bonded to each treated plate. All bonded specimens were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
6
29
0
1
Order By: Relevance
“…However, HF etching is less effective at zirconia3. Recently, several studies revealed that to be effective HF etching of zirconia requires a longer application time, a higher concentration of HF and/or a higher temperature, such as 9.5% HF at 80 °C for 1 min or at 25 °C for 1 h, or 48% HF at 25 °C for 30 min4, 20% or 30% HF for 30 min5, or 48% HF at 100 °C for 25 min6. Therefore, recent investigations have recommended alumina air-abrasion to increase the bond strength of composite cement to zirconia; it increases the surface area for micro-mechanical interlocking78.…”
mentioning
confidence: 99%
“…However, HF etching is less effective at zirconia3. Recently, several studies revealed that to be effective HF etching of zirconia requires a longer application time, a higher concentration of HF and/or a higher temperature, such as 9.5% HF at 80 °C for 1 min or at 25 °C for 1 h, or 48% HF at 25 °C for 30 min4, 20% or 30% HF for 30 min5, or 48% HF at 100 °C for 25 min6. Therefore, recent investigations have recommended alumina air-abrasion to increase the bond strength of composite cement to zirconia; it increases the surface area for micro-mechanical interlocking78.…”
mentioning
confidence: 99%
“…Contact angle tensiometer (Theta Lite, Dyne Technology, Staffordshire, UK) was used to estimate the differences in contact angle between grit-blasted ZrO 2 surfaces at different air pressures. The water contact angle was measured after 30 s according to the study protocols 7,16) .…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…Today, yttria (Y2O3)-stabilized polycrystalline tetragonal zirconia (Y-TZP) is a frequently used ceramic material for fixed prosthodontics, largely because of its favorable mechanical properties 7,8) . However, the relative inertness of ZrO2 renders its surface less reactive 7,9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisas têm sido desenvolvidas na perspectiva de utilização de ácidos em concentrações e tempos distintos para promover micromodificações na superfície da zircônia e favorecer o processo de adesão (Zarone et al, 2006;Xie et al, 2013;Menani et al, 2014;Sriamporn et al, 2014;Zandparsa et al, 2014;Lee et al, 2015;Cho et al, 2017). Menani et al, 2014, mostraram que o ácido fluorídrico 40% (HF 40%) aplicado por 210 segundos na superfície da Y-TZP foi capaz de aumentar significativamente a resistência adesiva à dentina bovina quando utilizado em associação ao cimento resinoso Panavia F. Ácidos com concentrações elevadas parecem ser capazes de condicionar a superfície de zircônia, promover microretenções e favorecer o processo de adesão.…”
Section: Elaborada Pela Biblioteca Central Do Campus Usp -Ribeirão Pretounclassified